Online Project Writing Training in Turkey: Virtual Learning Competencies and Participant Opinions - Bal İncebacak, Belgin; Yaman, Süleyman; SARIŞAN TUNGAÇ , Aslı (Journal of Interdisciplinary Studies in Education, 2023)
This study is an outcome of the Project Preparation Course project II for graduate students in the field of Educational Sciences conducted within the framework of the TUBITAK (Scientific and Technological Research Council of Turkey) 2237-A program to support scientific educational activities. In this course, training is integrated to student-centred and work-integrated learning was conducted. The study group consists of a total of 24 students, studying at 17 different universities. The research is structured in the form of a one-group pre-test post-test experimental design. Data collection tools are the project-based virtual learning competencies scale and the structured interview form. At the end of the project, it was found that participants expressed positive opinions about all the processes involved in the project. At the end of the project, work integrated learning based online course was found to positively impact the participants' project based virtual learning competencies.